SIKAP ORANG TUA TERHADAP ANAK YANG TIDAK MELANJUTKAN PENDIDIKAN KEJENJANG YANG LEBIH TINGGI DI DESA BEDENG SIKURAN KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Yogi Pratama Pratama; Aswandi Bahar Bahar; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: The problem in this research is: What is the attitude of parents of children who do not continue their education to a higher level. This study aims: To determine the attitude of parents of children who do not continue their education to a higher level. This research is deskrpitif with a quantitative approach, this method aims to provide a systematic overview of the state of the ongoing research on the object of the attitude of parents of children who do not melanjuttkan education to a higher level. Where the research is in the village of the District Inuman Bedeng Sikuran. The population in this study were parents in the village of the District Sikuran Bedeng Inuman, which amounted to 110 people, while a sample of 52 parents. The results showed that: Attitudes Parents of children who do not continue education to a higher level classified as Good. It is proved from the results of recapitulation of data, namely: 1.Komponen Cognitive respondents agreed amounted to 44.15%. 2. Affective component respondents saying Agree at 48.67% 3. Component Conative respondents agreed amounted to 45.05%. Keywords: Attitudes, Parents, Children, Education